Measurement of urinary malondialdehyde levels as an indicator of oxidative stress and free radical injury in schizophrenic patients [Şizofreni hastalarında oksidatif stres ve serbest radikal hasarının göstergesi olarak İdrarda malondialdehit ölçümü] - (:unkn) unknown (Marmara University, 2012)
Objective: The idea that oxidative stress has a significant role in development and prognosis of many diseases is being more widely accepted by the authorities. This study aims to examine urinary malondialdehyde assays and their concordance with other oxidative stress biomarkers in schizophrenic patients who have a highly stressful life due to their illness. Patients and Methods: Participants were 20 schizophrenic patients who were being followed by Marmara University Medical School Hospital outpatient clinic and 21 healthy controls. Blood and urine samples were examined for oxidative stress parameters. Results: Our results indicate that oxidized glutathione and plasma and urine malondialdehyde levels of patients were higher than those of control group. Urinary and plasma malondialdehyde levels showed a significant correlation especially in the patient group. Conclusions: If the study is supported by additional studies and repeated with higher sample sizes the urinary malondialdehyde assay which is an easy and cheap method, may be used as an oxidative screening test and thus may prove to be useful for preventing oxidative stress dependent diseases and developing new pharmacological agents. © Marmara Medical Journal, Published by Galenos Publishing.
Keywords: Malondialdehyde; Oxidative stress; Schizophrenia; Urine